Instant Energy Barrier Modulation in Bistable Robotic Grippers for Compliant Triggering and Powerful Grasping - Jie Zhang; Hao Yang; Chenyu He; Hanfei Ma; Yuwen Zhao; Zongyu Zhang; Shengming Li; Wei Wang; Jinzhao Yang; Jianing Wu; Haijun Peng (Research)
Bistable structures, which leverage mechanical instability, have emerged as a promising paradigm in the development of robotic grippers, providing advantages including rapid response and low energy consumption. A critical limitation of existing bistable grippers, however, lies in their invariable energy barriers, which hinder the balance between compliant triggering and powerful grasping. In this study, we propose a bistable robotic gripper capable of in situ energy barrier modulation, inspired by the adaptive seed dispersal behavior of Impatiens pods. This robotic gripper features an elastic curved beam-based architecture integrated with a motor-driven mechanism, enabling dynamic regulation of its energy landscape. This approach allows the energy barrier to be tuned over an order of magnitude during manipulation. In the low-barrier state, the robotic gripper initiates object interaction with a triggering force as low as 0.66 N, allowing for delicate manipulation. Upon state transition, instant energy barrier modulation (~300 ms) enhances grasping stability, achieving failure forces up to 12.08 N. This adaptive modulation strategy enables our robotic gripper to implement rapid, compliant, and powerful interaction. When incorporated into an unmanned aerial vehicle, the robotic gripper showcases reliable perching across diverse scenarios, highlighting the potential of energy barrier modulation to advance the adaptability and functionality of robotic systems.